PENDIDIKAN AGAMA ISLAM BERWAWASAN LINGKUNGAN HIDUP - Siti Yumnah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2020)
In fact, if we reflect and re-understand the verses of the Koran, it has become clear that natural disasters and environmental crises are the result of human activity. Environmental damage has long been pointed out in the Koran. In Islam's view, human beings are actually Allah's creatures assigned as caliphs, as regulators, and maintainers of this earth. But the grievous reality that is happening right now is that it is increasingly complex and leads to uncontrolled conditions with increasing world population growth that exceeds the natural productivity capacity of the earth. A large population is a potential for advancing the country, but if it is not balanced with an adequate level of understanding of ecology then it means disaster. Humans now have openly exploited the natural resources on earth and forced the earth to give more than what the earth produced according to its capacity. So this is where the role of Islamic education is needed as a reminder and bearer of good news to humans so that they are always obedient and obedient to Allah's commands to be able to be a caliph who is able to preserve the environment on earth along with other creatures.